Risk-to-befit ratios of consecutive antidepressants for heavy menstrual bleeding in young women with bipolar disorder or major depressive disorder - Zhuo, Chuanjun; Chen, Guangdong; Lin, Chongguang; Ping, Jing; Zhu, Jingjing; Wang, Lina; Jin, Shili; Liu, Chuanxin; Zhang, Qiuyu; Yang, Lei; Li, Qianchen; Zhou, Chunhua; et al. (Frontiers in Psychiatry, 2022)
Induction of heavy menstrual bleeding (HMB) by pharmacological agents has been reported in young adult women. The aim of this study was to investigate a possible relationship between occurrence rates of HMB and different categories of treatment methods (e.g., antidepressant agents alone and in combination with other pharmacological agents). The cohort examined included young women (18–35 y, n = 1949) experiencing bipolar disorder (BP) or major depressive disorder (MDD). Twenty-four months of menstruation history for these women were recorded and evaluated according to pictorial blood loss assessment charts of HMB. Multivariate analyses were conducted to obtain odds ratios (ORs) and 95% confidence intervals (CIs). The antidepressant agents examined exhibited varying ORs in BP versus MDD patients. For example, the OR of venlafaxine-induced HMB was 5.27 in patients with BP and 4.58 in patients with MDD. For duloxetine, it was 4.72 and 3.98; for mirtazapine, 3.26 and 2.39; for fluvoxamine, 3.11 and 2.08; for fluoxetine, 2.45 and 1.13; for citalopram, 2.03 and 1.25; for escitalopram, 1.85 and 1.99; for agomelatine, 1.45and 2.97; for paroxetine, 1.19 and 1.75;for sertraline, 0.88 and 1.13; for reboxetine, 0.45 and 0.45; and for bupropion, 0.33 and 0.37, respectively in each case. However, when antidepressant use was combined with valproate, the OR of HMB greatly increased, with distinct profiles observed for BP versus MDD patients. For example, the OR of HMB for venlafaxine combined with valproate was 8.48 in patients with BP and 6.70 in patients with MDD. For duloxetine, it was 5.40 and 4.40; for mirtazapine, 5.67 and 3.73; for fluvoxamine, 5.27 and 3.37; for fluoxetine, 3.69 and 4.30; for citalopram, 5.88 and 3.46; for escitalopram, 6.00 and 7.55; for agomelatine, 4.26 and 5.65; for paroxetine, 5.24 and 3.25; for sertraline, 4.97 and 5.11; for reboxetine, 3.54 and 2.19; and for bupropion, 4.85 and 3.46, respectively in each case. Thus, some antidepressant agents exhibited a potential risk for inducing HMB. Furthermore, a combined prescription of antidepressant agents and valproate should be carefully considered for young women with HMB.